2015
DOI: 10.1016/j.gca.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Formation and transformation of a short range ordered iron carbonate precursor

Abstract: Fe(II)-carbonates, such as siderite, form in environments where O 2 is scarce, e.g., during marine sediment diagenesis, corrosion and possibly CO 2 sequestration, but little is known about their formation pathways. We show that early precipitates from carbonate solutions containing 0.1 M Fe(II) with varying pH produced broad peaks in X-ray diffraction and contained dominantly Fe and CO 3 when probed with X-ray photoelectron spectroscopy. Reduced pair distribution function (PDF) analysis shows only peaks corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
52
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 57 publications
8
52
1
Order By: Relevance
“…1, bottom; Table DR1 in the Data Repository). Our detailed mineralogical analyses show that the siderites are highly ordered, and we did not detect the amorphous carbonate precursors of siderite that are commonly observed in laboratory experiments (Sel et al, 2012;Dideriksen et al, 2015).…”
Section: Diagenetic Sideritescontrasting
confidence: 49%
“…1, bottom; Table DR1 in the Data Repository). Our detailed mineralogical analyses show that the siderites are highly ordered, and we did not detect the amorphous carbonate precursors of siderite that are commonly observed in laboratory experiments (Sel et al, 2012;Dideriksen et al, 2015).…”
Section: Diagenetic Sideritescontrasting
confidence: 49%
“…Replicating these in batch cultures with natural abundances of multiple microbial populations has been challenging. Furthermore, the nucleation pathway for siderite is unclear, for example, whether there is a less stable carbonate precursor to siderite such as amorphous calcium carbonate (ACC), amorphous iron (II) carbonate (AFC) (Dideriksen et al, ; Jiang & Tosca, ; Sel et al, ) or monohydrocalcite (MHC) and whether siderite (both nodular or laminated) is then made during the transformation of these precursors to stable phases in the presence of dissolved iron. Understanding this mechanism for siderite formation may provide insights as to how changes in fluid chemistry impact the formation of various carbonate polymorphs during non‐classical nucleation in an iron‐dominated system and what environmental or biological conditions can be indicated by the presence of nodular/spheroidal and laminated siderite in the geological record.…”
Section: Introductionmentioning
confidence: 99%
“…Replicating these in batch cultures with natural abundances of multiple microbial populations has been challenging. Furthermore, the nucleation pathway for siderite is unclear, for example, whether there is a less stable carbonate precursor to siderite such as amorphous calcium carbonate (ACC), amorphous iron (II) carbonate (AFC) (Dideriksen et al, 2015;Jiang & Tosca, 2019;Sel et al, 2012) or monohydrocalcite (MHC) and whether siderite (both nodular or laminated) is then made during the transformation of these precursors to stable phases in the presence of dissolved iron.…”
mentioning
confidence: 99%
“…For example, crystal growth assisted by structured pre-crystalline states (Gebauer et al, 2008;Dey et al, 2010;Demichelis et al, 2011), nucleation from metastable phases (Chung et al, 2009;Washington et al, 2012;Baumgartner et al, 2013;Maes et al, 2015), oriented attachment of crystallites (Banfield et al, 2000;Li et al, 2012;Nielsen et al, 2014), and growth emerging out of amorphous phases (Weiss et al, 2002;Politi et al, 2004;Killian et al, 2009;Savage and Dinsmore, 2009;Mahamid et al, 2010;Lechner et al, 2011;Salvalaglio et al, 2014;Ma et al, 2017;Pendola et al, 2018) have all been shown to alter growth in non-trivial ways, often resulting in complex structure formation that appear to defy the evolution of the system toward its ultimate lowest energy configuration. Moreover, these types of alternative growth mechanisms have been suggested in systems with widely different environmental conditions, from biological context such as protein crystal nucleation (Vekilov and Vorontsova, 2014), calcite growth (Weiss et al, 2002;Politi et al, 2004;Killian et al, 2009;, tissue mineralization (Wang et al, 2012;Weaver et al, 2012;Tao et al, 2019), magnetite nucleation and growth (Kuhrts et al, 2019;Mirabello et al, 2019;Rawlings et al, 2019), as well as inorganic contexts like cadmium selenide quantum dot growth (Washington et al, 2012), iron oxide growth (Banfield et al, 2000;Baumgartner et al, 2013;Dideriksen et al, 2015), and colloidal microparticle crystallization (Savage et al, 2...…”
Section: Introductionmentioning
confidence: 99%